Postoperative Adjuvant Chemotherapy Regimen of CAPOX Combined With Ninjin'yoeito in an Elderly Patient With Stage III Colon Cancer: A Case Report - Aomatsu, Naoki; Uchima, Yasutake; Tsujio, Gen; Miyamoto, Yoshinari; Okada, Takuma; Kurihara, Shigeaki; Matsutani, Shinji; Hirakawa, Toshiki; Iwauchi, Takehiko; Morimoto, Junya; Yamagata, Shigehito; Nakazawa, Kazunori; et al. (Frontiers in Nutrition, 2020)
We report the successful management of stage Ⅲ colon cancer in an elderly patient with adjuvant chemotherapy of CAPOX combined with ninjin’yoeito. A 75-year-old woman visited another hospital because of fecal occult blood. Colonoscopy revealed a type Ⅱ tumor in the Sigmoid colon. She was referred to our hospital for tumor resection. She had a medical history of hypertension. Colonoscopy revealed a type II tumor located 23 cm from the anal verge in the sigmoid colon. Histopathological findings of the biopsy specimen of the sigmoid colon tumor revealed moderately differentiated tubular adenocarcinoma. Thoracic and abdominal enhanced computed tomography showed the wall thickness of the sigmoid colon. Regional lymph node metastasis was suspected, but there were no findings of distant metastasis. Blood examination revealed no abnormalities, except for the level of carcinoembryonic antigen (CEA) (32.7 ng/ml). We therefore diagnosed it as clinical stage Ⅲb cancer [cT4a, N1b, M0] of the sigmoid colon. Laparoscopic sigmoid colectomy was performed without complications. The postoperative histopathological examination revealed a moderately differentiated to mucinous adenocarcinoma. Sixteen lymph nodes were retrieved, and three of them contained malignant cells. It was classified as pT4a pN1b M0 pStageⅢb. The patient recovered uneventfully and was discharged 10 days after the surgery. Being diagnosed with a stage III colorectal cancer, the patient was proposed adjuvant chemotherapy with capecitabine plus oxaliplatin (CAPOX) starting 4 weeks after surgery. The patient received 7.5 g of ninjin’yoeito (NYT) daily from the start to the end of adjuvant chemotherapy. Peripheral neuropathy, neutropenia and febrile neutropenia were not reported. She has not experienced any recurrence for one years after the surgery. NYT is a Japanese kampo medicine prescribed and clinically admired in Japan. In our elderly stage Ⅲ colorectal cancer case, adjuvant CAPOX chemotherapy combined with NYT was completed without adverse effects such as appetite loss, peripheral neuropathy, neutropenia, and febrile neutropenia. NYT might therefore be useful for reducing the adverse effects of anticancer therapy, particularly in the elderly.